Abies sachalinensis naturally growing at a sedimentary site acquires iron tolerance via detoxicants production, elemental transfer adjustment, and root endophytic Phialocephala bamuru producing siderophores - Toshikatsu Haruma; Hayato Masuya; Keiko Yamaji; Yosuke Yamamoto; Naoto Nishimoto; Takahiko Arima; Shingo Tomiyama (PLoS ONE, 2025)
Abies sachalinensis naturally growing in heavy metal-rich sedimentary sites exhibits heavy metal tolerance. Although root endophytes increase heavy metal tolerance in various plants, their effects on the tolerance in conifers are not focused on. The objective of our study was to clarify the heavy metal tolerance, considering root endophytes. We measured the heavy metal concentrations in root-zone soil, leaves, stems, fine roots along with heavy metal detoxicants. We also isolated root endophytes and identified the endophyte with the highest siderophore production activity for chelating heavy metals. Results showed high Fe accumulation in fine roots, where malic acid, catechin, and condensed tannins detoxify Fe. A lower Fe/Mn ratio in leaves than roots suggests that A. sachalinensis could regulate Fe and Mn transfer to mitigate Fe phytotoxicity in leaves. Among the isolated root endophytes, Phialocephala bamuru exhibited the highest siderophore production, which could detoxify Fe in A. sachalinensis. These results indicated that A. sachalinensis have multiple Fe tolerance: Fe detoxification production and Fe/Mn ratio adjustment. Moreover, interactions with root endophytes like Ph. bamuru producing siderophores could increase the Fe tolerance and facilitate revegetation on soil containing heavy metal like old mine sites by conifers including A. sachalinensis.